Institutionalizing Identity: Symbolic Isomorphism and Organizational Names - Glynn, Mary Ann; Abzug, Rikki (Academy of Management Journal, 2002)
An organization's identity, symbolized by its corporate name, is rooted in institutional fields. We advance the construct of symbolic isomorphism, or the resemblance of an organization's symbolic attributes to those of others within its institutional field, and examine its effects on the homogenization of names and legitimacy. We review historical naming patterns and present two studies that examine the antecedents and outcomes of name conformity: The first analyzes 1,600 name changes to demonstrate how institutional conformity shapes organizational identities, and the second surveys public audiences and delineates how symbolic isomorphism serves as a touchstone for legitimacy.